Nia Imani Model of Care's Impact on Homeless African-American Women. (December 2020) - Dressel, Anne; Hawkins, Maren; Lopez, Alexa A.; Pittman-McGee, Belinda; Kako, Peninnah; Gakii, Dorothy; Mkandawire-Valhmu, Lucy
This qualitative study assessed the impact of the Nia Imani model of care on homeless African-American women, many of whom abused drugs, experienced interpersonal violence, and faced other challenges when seeking to improve their lives and health. Nia Imani Family, Inc., is Milwaukee, Wisconsin's, only long-term transitional living facility. Grounded in Black feminist thought, our study included focus group interviews with 39 women who had lived at Nia Imani, and successfully completed its programs; and one individual interview with the founder, who had also experienced homelessness (N=40). Themes were identified through thematic analysis, and included the following: crucial social support, learning self-worth, stability and structure, appreciation for strict rules, and importance of parenting and financial literacy classes. To ensure effective interventions, there is a need for nurses to understand how community-based and community-led programs, like Nia Imani, impact the health and well-being of African-American women, who have experienced homelessness.